Euroregion as the highest organizational and functional level of cross-border cooperation - Tsekhanovych, Victor (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
In modern conditions of expanding the processes of globalization the role of globalization is growing cross-border cooperation of regions, which opens up new opportunities for activation of economic activity in the peripheral territories and increase of economic activity in the peripheral territories their competitiveness. At the end of the last century, the regional the policy of the European Union has moved to a new paradigm-from application of mechanisms to eliminate regional development imbalances through interregional redistribution of resources to mobilization of course-resource potential of territories and application of the principle of subsidiarity. This one the approach was used by the contiguous border regions of Europe, which we have established mutual contacts between state and regional authorities, local self-government bodies, public organizations, and subjects management of territories, joining forces to solve common problems, and from cooperation under certain cross-border agreements we have moved on to cooperation within the framework of euroregions. Thus, the characteristic a feature of modern Europe is the rapid development of international cooperation regions – one of the most effective driving forces of European integration and bringing people together. Cross-border cooperation should be implemented in the context of territorial organization and effective deployment of productive forces. According to European experience, the CBC helps to overcome the territorial imbalance (spatial gaps between production and consumption) of the region’s economy, which is a significant factor, since there are significant developmental imbalances between the border administrative-territorial units of Ukraine and neighboring states. The implementation of this task in practice is carried out by complementarity, improvement and optimization of the territorial structure of the economy, functional combination and coordination of economies, industries and individual industries of border regions of neighboring states involved in cross-border cooperation. Along with this, it is fundamental to maintain a balance (optimal proportions) in the development of all spheres of life of territories on different sides of the border.